A new method to characterize underlying scratches on SiC wafers. Issue 7 (29th January 2019) - Zhang, Zesheng; Cai, Hao; Gan, Di; Hu, Weijie; Yang, Junwei; Liu, Xiaozhi; Guo, Yunlong; Guo, Liwei; Wang, Wenjun; Chen, Xiaolong
Abstract : The underlying scratches are revealed after quick irradiation using a picosecond pulsed laser; otherwise, they are unseen under an optical microscope. Abstract : We report a new method to reveal the underlying scratches that are usually unseen under optical microscopy on SiC wafers after chemo-mechanical polishing (CMP) treatment. After scanning Si terminated surfaces using a picosecond pulsed laser (355 nm) for a short duration, the scratches are clearly revealed under an optical microscope. The damage thresholds by the picosecond pulsed laser are obtained for 4H- and 6H-SiC. We demonstrate that this method is equally effective in unravelling these underlying scratches as other existing state-of-art methods including those etched by molten KOH at about 400–500 °C. The method is quick, facile, less-destructive and sensitive in characterizing the underlying surface scratches. It has great potential to find practical application in quality control for SiC wafers.